Reconstruction of Upper Cervical Spine and Craniovertebral Junction - Suchomel, Petr; Choutka, Ondrej (Springer Berlin Heidelberg : Imprint: Springer, 2011)
An illustrative manual for general spine surgeons, this text atlas covers all currently available techniques of upper cervical spine and craniovertebral junction reconstruction. All the surgical risks and benefits are discussed and compared with the outcome of more than 300 surgeries of this region. The surgical procedures are demonstrated step-by-step in instructive drawings and illustrations describing the approach, technique of implant introduction and spine reconstruction. A special focus is on realtime and virtual navigation techniques as well as potential complications and their avoidance.